THE STRUCTURE OF POEM IN TALE KERINCI FOLKLORE - Nazurty, Nazurty; Rafli, Zainal (PPs UNJ, 2015)
Tale is the folklore in the form of poem that is sung. This study aims to gain in-depth understanding of the structure of Tale poem in the release of the Kerinci pilgrims. This qualitative study employed content analysis as the method with a structural approach. This study discussed the structure of the Tale poem. The results of the study are Tale poem consists of sampiran phrase, the rhyme/ sound phrase, and content. It composed by ten lines to twenty lines. It has ab ab rhyme according to the sound phrase flanking each line. The sound expression serves as rhyme and rhythm former.